Neck Loads During Head-First Entries into Trampoline Dismount Foam Pits: Considerations for Trampoline Park Safety - Tom Whyte; Edward Lind; Adam Richards; David Eager; Lynne E. Bilston; Julie Brown (Annals of Biomedical Engineering, 2022)
Serious cervical spine injuries have been documented from falls into foam pits at trampoline parks. To address the lack of evidence on how foam pits should be designed for mitigating neck injury risk, this study aimed to quantify neck loads during head-first entry into varying foam pit designs. An instrumented Hybrid III anthropomorphic test device was dropped head-first from a height of up to 1.5 m into three differently constructed foam pits, each using a different mechanism to prevent direct contact between the falling person and the floor (foam slab, trampoline or net bed). Measured neck loads were compared to published injury reference values. In the simplest, foam-only pit design, increasing foam depth tended to reduce peak compressive force. At least one injury assessment reference metric was exceeded in all pit conditions tested for 1.5 m falls, most commonly the time-dependent neck compression criterion. The results highlight the importance of adequate foam depth in combination with appropriate pit design in minimizing injury risk. The risk of cervical spine injury may not be reduced sufficiently with current foam pit designs.

Characterization of the microbial community structure and the physicochemical properties of produced water and seawater from the Hibernia oil production platform - C. William Yeung; Kenneth Lee; Susan Cobanli; Tom King; Jay Bugden; Lyle G. Whyte; Charles W. Greer (Environmental Science and Pollution Research, 2015)